228k views
5 votes
Match the equation with the step needed to solve it.

1. 2m - 1 = 3m

subtract 2

2. 2m = 1 + m

subtract 1

3. m - 1 = 2

add 1

4. 2 + m = 3

subtract m

5. -2 + m = 1

add 2

6. 3 = 1 + m

subtract 2m

User Aspire
by
5.4k points

2 Answers

2 votes

Answer:

The other person is correct!!!

Explanation:

I just had this assingment graded.

User ThinkingInBits
by
4.9k points
6 votes
Each one is a step to isolate the variable.
Subtract 2 goes to step four as you have to move 2 to the other side to isolate the m.
Making it M=3-2
Subtract 1 goes to 6
3-1=m
Add 1 goes to 3
Subtract m goes to 2
Add 2 goes to 5
Subtract 2m goes to 1
User Blueboye
by
5.5k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.